Implementation Measurement of Physical Test Results for Branch of Badminton Using Application - Irawati, Windi Setya; Hartati, Hartati; Yusfi, Herri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The study aims to assess the physical fitness of students at State Elementary School 216 Palembang through the use of an application for measuring physical test results. The research employs a quantitative descriptive method. The findings from the application-based physical test measurements reveal that 16 students fall into the "good" category, constituting 66.7%, while 8 students fall into the "enough" category, representing 33.3%. Consequently, the overall physical condition of students at State Elementary School 216 Palembang is categorized as "good." A study conducted by Wiyanto (2020) has developed norms and physical condition tests specifically tailored for badminton players aged 10-12 years. These tests demonstrate validity, reliability, and effectiveness, recommending them as suitable measuring instruments for assessing physical fitness in badminton. The outcomes of this research underscore the importance of cultivating awareness among students and athletes to continually enhance and maintain their physical fitness for optimal performance. The application introduced in this study facilitates a more streamlined process for teachers, coaches, and athletes to gauge physical test results, enhancing the effectiveness and efficiency of monitoring the physical condition of students and athletes.